Linguagem e ideologia no discurso pentecostal - Magalhães, Izabel (Cadernos de Linguagem e Sociedade, 2010)
The purpose of this paper is to discuss the construction of the subject in Pentecostal discourse by means of a language whose basic aim is to control followers, under the guise of offering them support. A therapeutic-disciplinary ideology is focussed on in an analysis of noun phrases, which frame a world of absolute values. Adopting the theoretical framework of Criticai Discourse Analysis and an interpretative ethnographic methodology, this research, carried out in Brasília in 1991-1992, had the following results: Pentecostal discourse, a combination of charismatic religious discourse and an institutionalised form of Protestantism, has succeeded in attracting followers by valuing consumer goods, enterprises and enterprisers. In addition, Pentecostal discourse derives its success from a therapeutic technique used to liberate people from anxiety and to animate social groups led into a process of anomy by their disbelief and lack of prospect in the future. In this sense, therapeutic discourse technologies, such as singing, preaching and blessing, have contributed to neutralise daily tensions, as well as to support the unemployed and to solve family crises. In such a therapeutic process, language plays a crucial role in ordering experience, mobilising and classifying meaning. The paper indicates that noun phrases classify mythical experience in terms of good and evil. In such a linguistic process, one notes that Pentecostal discourse represses and manipulates groups of the population, mainly that of women.